SMART INDUSTRY: INNOVATIONS AND CHALLENGES ON THE PATH TO EFFICIENT PRODUCTION - Білоус-Сергеєва, С.О. (SWorldJournal, 2023)
Today, the industry faces significant challenges related to increased competition, economic instability and growing consumer demands. In order to cope with these challenges and ensure the efficient and competitive operation of the company, it is necessary